Direct access to α-sulfenylated amides/esters via sequential oxidative sulfenylation and C–C bond cleavage of 3-oxobutyric amides/esters. Issue 7 (8th January 2018) - Jiang, Yi; Deng, Jie-dan; Wang, Hui-hong; Zou, Jiao-xia; Wang, Yong-qiang; Chen, Jin-hong; Zhu, Long-qing; Zhang, Hong-hua; Peng, Xue; Wang, Zhen
Abstract : An efficient, environmentally benign and unprecedented synthesis of various α-sulfenylated amides/esters has been developed under oxygen atmosphere. Abstract : An efficient, environmentally benign and unprecedented synthesis of various α-sulfenylated amides/esters has been developed under oxygen atmosphere. The reaction shows good functional group tolerance and excellent chemo/regioselectivity. All the desired products were obtained in moderate to excellent yields, even on the gram scale. Practically, the related α-thiol Weinreb amide can be readily transferred to a series of prospective compounds, and selenium atom can be introduced to the α-sites of the amides in high yields.